Effects of lifestyle intervention on weight and metabolic parameters in patients with impaired glucose tolerance related to beta‐3 adrenergic receptor gene polymorphism Trp64Arg(C/T): Results from the Japan Diabetes Prevention Program. Issue 3 (29th October 2015) - Sakane, Naoki; Sato, Juichi; Tsushita, Kazuyo; Tsujii, Satoru; Kotani, Kazuhiko; Tominaga, Makoto; Kawazu, Shoji; Sato, Yuzo; Usui, Takeshi; Kamae, Isao; Yoshida, Toshihide; Kiyohara, Yutaka; et al.
Abstract: The beta‐3 adrenergic receptor (ADRB3), primarily expressed in adipose tissue, is involved in the regulation of energy metabolism. The present study hypothesized that ADRB3 (Trp64Arg, rs4994) polymorphisms modulate the effects of lifestyle intervention on weight and metabolic parameters in patients with impaired glucose tolerance. Data were analyzed from 112 patients with impaired glucose tolerance in the Japan Diabetes Prevention Program, a lifestyle intervention trial, randomized to either an intensive lifestyle intervention group or usual care group. Changes in weight and metabolic parameters were measured after the 6‐month intervention. The ADRB3 polymorphisms were determined using the polymerase chain reaction restriction fragment length polymorphism method. Non‐carriers showed a greater weight reduction compared with the carriers in both the lifestyle intervention group and usual care group, and a greater increase of high‐density lipoprotein cholesterol levels than the carriers only in the lifestyle intervention group. ADRB3 polymorphisms could influence the effects of lifestyle interventions on weight and lipid parameters in impaired glucose tolerance patients. Abstract : The non‐carriers showed significantly greater reductions of weight and BMI than the carries both in ILG and UCG. On the other hand, both being a carrier and lifestyle intervention had significant influences on HDL‐C levels. The non‐carriers showed a significantly greater increase of HDL‐C levels than carries only in the ILG. Except for weight and HDL‐C, changes of other parameters were not significantly affected by Trp64Arg polymorphisms.